Peran Pemeriksaan Laboratorium dalam Penegakan Diagnosis Penyakit Kusta - Arleen Devita (Jurnal Kedokteran Meditek, 2018)
Leprosy is one of serious health problems in the world, particularly in Indonesia, which reportedly is the third highest number of leprosy cases in the world. This disease is a contagious disease caused by Mycobacterium lepra. The symptoms and clinical signs resemble to other skin diseases, so often that it is referred as the great imitator. The diagnosis of leprosy is generally established by anamnesis and physical examination. However, in certain cases with vague clinical sign and symptoms, i.e. in early cases of leprosy, laboratory examination such as microscopic, histopathologic, serologic and molecular examinations, is needed to establish the diagnosis.Keywords : leprosy diagnostic, Microscopic examination, Histopathologic examination, Serologic examination and Molecular examination.